A Comparative Study of Pseudomonas aeruginosa and Bacillus subtilis Ability in Biodegradation Process of Kerosene Contaminated Soil - Paramata, Mulyani Zahra (Jambura Journal of Chemistry, 2023)
Kerosene is a type of hydrocarbon commonly known as paraffin oil which is usually used as a home heating fuel, lamp and asphalt solvent. The presence of kerosene in the asphalt production can potentially cause environmental pollution, one of which affects soil conditions. Some bacteria that have specific ability to degrade hydrocarbon content in soil are called hydrocarbonoclastic bacteria. Pseudomonas Aeruginosa and Bacillus Subtilis are two types of bacteria that belong to the type of hydrocarbonoclastic bacteria. This study aims to compare the ability of the two types of bacteria to decrease the concentration of kerosene in this case measured as Total Petroleum Hydrocarbon (TPH) on artificial soil with a ratio of sand to asphalt material containing kerosene of 75:25 for 10 days of testing. Other supporting parameters used in this study were temperature, pH, water content. Based on the results of the study, the temperature and pH values of the soil measured for 10 days ranged between the normal and optimum ranges for the biodegradation process. Meanwhile, the soil media had low water content compared to the optimum conditions for the biodegradation process. However, hydrocarbon compounds still naturally degraded due to environmental factors even though the rate of degradation was slow. Based on the descriptive analysis method, it was found that the ability of Pseudomonas Aeruginosa in degrading kerosene was 54.67% and for Bacillus Subtilis it was 62.62%. It can be seen that there was a difference in the ability of the two types of bacteria in descriptive analysis, but different results were obtained in the results of statistical analysis where there is no significant difference between the two types of bacteria on the total percentage of TPH reduction in the soil.